BEAUTIFUL PLACES AND RECREATING HUMANITY IN SOUTH AFRICA - G.J. Van Wyngaard (Acta Theologica)
The article investigates the connection between beauty and justice, by exploring everyday aesthetics through ordinary life, specifically the very concrete reality of contemporary urban South Africa. On the one hand, it delves beneath the statement that apartheid is ugly, by exploring the ugly spaces apartheid created, the devastation of an aesthetic built on segregation, and the distortions of whiteness. It also seeks to explore a theological aesthetic that starts from the ordinary life lived in particular places, arguing that beauty in particular places must be interwoven with humanness in all places, and proposing a theological aesthetic that gives priority to the voices silenced in particular places. Through this, beauty and justice are intimately interwoven in the ongoing work of disruption and transformation of a white racist place.